N-type In2S3 films deposited by pulsed laser deposition: effect of laser power on the properties of the films. (19th May 2015) - Wu, Chunyan; Mao, Dun; Liu, Zhu; Liang, Qi; Chen, Shirong; Yu, Yongqiang; Wang, Li; Luo, Linbao; Xu, Jun
Abstract: Pulsed laser deposition (PLD) with different levels of laser power was first used to deposit In2 S3 films from homemade, high-purity In2 S3 targets. This process was followed by post-annealing in an N2 atmosphere to improve the films' crystallinity and conductivity. The annealed films were verified to be stoichiometric, body-centered, tetragonal In2 S3 with the preferred orientation (103). The bandgap of the films decreased from 2.8 to 2.2 eV with an increase in the laser power, which was believed to be the result of the grain growth caused by the higher laser power. The electrical transport property of the bottom-gate field-effect transistor revealed the n-type conduction of the annealed In2 S3 films, and the heterojunction p + -Si/annealed In2 S3 film showed remarkable photovoltaic behavior upon light illumination, indicating that PLD-deposited In2 S3 films may have great potential as a buffer layer in thin-film solar cells. What's more, doped In2 S3 films can be easily realized due to the fairly stoichiometric transfer of the PLD method.